THE CHALLENGES OF EDUCATION: EXPERIENCES THAT WORKED - Teixeira, Maria Luiza Gomes (Seven Editora, 2024)
This article intends to present the psychopedagogical work adopted by the Center for Guidance and Psychopedagogical Care - NOAP PUC-Rio, through some reports of sessions carried out by volunteer psychopedagogues. This Center has been working with children and adolescents, students from public schools, for more than 40 years, with the challenge of rescuing the desire to be in school, providing a healthier development. During the pandemic, the team sought alternatives and methodologies so as not to interrupt the flow of care, which guaranteed, for many children and adolescents, the only learning space.NOAP also works with schools and teachers.In this article, we focused on showing how NOAP seeks to continue this service through alternative methodologies. DOI:https://doi.org/10.56238/sevened2024.027-010